GAS CHROMATOGRAPHY-MASS SPECTROMETRIC ANALYSIS OF ETHANOLIC EXTRACTS OF GLYCYRRHIZA GLABRA LINN. ROOTS. - U.VIJAYALAKSHMI; ABHILASHA SHOURIE (International Journal of Pharma and Bio Sciences, 2013)
Glycyrrhiza glabra is a plant with high medicinal and commercial value. Although several secondary metabolites have been reported from different species of this plant, there has been not much information available on the complete profile of phytochemical constituents in Glycyrrhiza glabra Linn. This study applies Gas Chromatography-Mass Spectrometry technique to determine the possible chemical components in the ethanolic extracts of Glycyrrhiza glabra roots and reports for the first time most extensive profile of the plant. In this analysis we found one hundred and twenty six compounds including flavonoids, terpenoids, saponins, essential oils, amino acids, and other nitrogen containing compounds, hydrocarbons, fatty acids and their esters. The most abundant phytoconstituents identified were 5-(Hydroxymethyl)-2-furancarboxaldehyde (23.15%), N-Methyl-4-(4-methyl-1-phthalazinylamino)-benzamide (7.18%), 2-Phenyl-furo[b]benzopyran-4(4H)-one (5.69 %) and 1, 2-Benzenedicarboxylic acid (5.31%). Most of the compounds in the list are said to possess medicinal properties which further justify the applications of this plant in the discovery of novel therapeutics.